Is It Time to Reconsider Postoperative Epidural Analgesia in Patients Undergoing Elective Ventral Hernia Repair?: An AHSQC Analysis. Issue 5 (May 2018) - Prabhu, Ajita S.; Krpata, David M.; Perez, Arielle; Phillips, Sharon; Huang, Li-Ching; Haskins, Ivy N.; Rosenblatt, Steven; Poulose, Benjamin K.; Rosen, Michael J.
Abstract : Objective: We aimed to evaluate the association of epidural analgesia (EA) with hospital length of stay (LOS), wound morbidity, postoperative complications, and patient-reported outcomes in patients undergoing ventral hernia repair (VHR). Background: EA has been shown to reduce LOS in certain surgical populations. The LOS benefit in VHR is unclear. Methods: Patients having VHR performed in the Americas Hernia Society Quality Collaborative (AHSQC) were separated into 2 comparable groups matched on several confounding factors using a propensity score algorithm: one group received postoperative EA, and the other did not. The groups were then evaluated for hospital LOS, 30-day wound morbidity, other complications, and 30-day patient-reported outcomes using pain and hernia-specific quality-of-life instruments. Results: A 1:1 match was achieved and the final analysis included 763 patients receiving EA and 763 not receiving EA. The EA group had an increased LOS (5.49 vs 4.90 days; P < 0.05). The rate of wound events was similar between the groups. There was an increased risk of having any postoperative complication associated with having EA (26% vs 21%; P < 0.05). Pain intensity-scaled scores were significantly higher (worse) in the EA group versus the non-EA group (47.6 vs 44.0; P = 0.04). Conclusions: The LOS benefit of EA noted for other operations may not apply to patients undergoing VHR. Further study is necessary to determine the beneficial role of invasive pain management procedures in this group of patients with an extremely common disease state.